Rector of the Polish Catholic Mission in England and Wales - NECEL, WOJCIECH (Prawo Kanoniczne, 2017)
The Bishops' Conference of England and Wales at the plenary session on 8 May 2014 accepted the newly developed regulations concerning the service of the Polish Canonical Mission rector in the Polish-language pastoral mission in England and Wales. The adopted regulations are placed in two compatible documents. The first is entitled "Structures and procedures the role of national coordinator for the Polish Catholic Mission In England and Wales", the second is entitled: "Principles for secular pristers and religious working within the Polish Catholic Mission In England and Wales". On the same date the President of the Bishops' Conference of England and Wales, Cardinal Vincent Gerard Nichols in a separate document confirmed the appointment of Rev. Msgr. Stefan Wylężek to the position of national coordinator/delegate vicar for priests engaged in pastoral work within the Polish Catholic Mission in England and Wales - Rector of the Polish Catholic Mission. In the context of the instruction Pontifical Council regarding Pastoral Care of Migrants and Itinerant People Erga Migrantes Caritas Christi in May 2004 in this paper examines the abovementioned documents